ABILITY TO READ QURAN AND UNDERSTANDING OF TAJWID FOR SRIWIJAYA UNIVERSITY STUDENTS - Sri Safrina; Muhammad Irfan (Conciencia, 2020)
The ability to read the Al Quran and understanding the tajwid are two things that cannot be separated. Good reading skills without understanding the knowledge of tajwid will make the reading misleading. This study aims to determine the ability to read AlQuran, the ability to understand tajwid, and the correlation between these two variables in Sriwijaya University students. This research data was taken from 100 new Sriwijaya University students in 2019 and analyzed using statistical methods. The results of this study indicate that the majority of Sriwijaya University new students (42%) have reading skills in the range of 64-71 values ​​and the majority of mastery of tajwid (36%) in the range of values ​​56-63. The results of this study also indicate that there was a significant correlation between the mastery of tajwid and the ability to read AlQuran with a correlation coefficient (r) of 0.98.